Implementation of Public Information Disclosure Regulations in An Electronic-Based Government System in Madiun City - Rizal Budi Arthanto; Anwar; Sigit Sapto Nugroho (Universitas Merdeka Madiun, 2025)
Abstract Introduction to the Problem: This research is very urgent to find out the implementation of regulations on public information disclosure in electronic-based information systems in Madiun City with various obstacles. Purpose/Study Objectives: The purpose of this study is to analyze the implementation of regulations on public information disclosure in electronic-based information systems in Madiun City and to analyze the weaknesses of regulations on public information disclosure in electronic-based information systems in Madiun City. Design/Methodology/Approach: The research method used in this study is legal sociology research (socio legal research), data sources in the form of primary data and secondary data and analyzed data using qualitative descriptive analysis. Findings: Based on the results of research and discussion shows that the implementation of public information disclosure regulations in electronic-based information systems in Madiun City carried out by the Implementing PPID of Madiun City can be seen that the average value of public information disclosure in the Implementing PPID of Madiun City reaches 95%. The indicators are there are no public information disputes and no objections and the number of complaints from the Madiun City Government related to the quality of services such as administrative services, indications of Corruption Crimes (Tipikor) and service officers is 0 (zero) or no complaints. Meanwhile, the weaknesses of public information disclosure regulations in electronic-based information systems in Madiun City are internally no obstacles but management is constrained by human resources, limited facilities and infrastructure; and expertise in the field of information and technology. The efforts made are by conducting periodic technical guidance and commitment to complete infrastructure facilities. Paper Type: Research Article